KAJIAN INTRUSI AIR LAUT DAN DAMPAKNYA TERHADAP MASYARAKAT DI PESISIR KOTA TEGAL - Ismawan, Moch Fajar (Geo-Image, 2016)
This study aims to analyze: (1) Distribution of sea water intrusion in the coastal city of Tegal, (2) Factors leading to sea water intrusion in the coastal city of Tegal, (3) Impact of sea water intrusion to coastal peoples in Tegal. The method used descriptive-quantitative. Data analyses used are descriptive analysis, comparative,overlay and weighting. The results showed the distribution of the effect of seawater intrusion higher by 1,343 Ha(34.3%), the effect of seawater intrusion middle of 498 Ha(12.7%), and is not affected by the intrusion of sea water for 2,072 Ha (53%). Sea water intrusion factors in Tegal include size of area ponds, groundwater increases, the characteristics of which is flat and sandy beaches, rock constituent alluvium soil and water fluctuations The impact of sea water intrusion to the community is to be a hard foaming wash water, for bathing feels sticky and each month should spend more money to buy suitable water for drinking. The longest distance the influence of sea water is 4 Km from the coastline. Broadness of farm land is the greatest influence that causes differences in sea water intrusion in Tegal city. Relevant agencies and the public to make the step to cope with the intrusion of sea water from spreading.